TRAINING SYSTEM FOR THE COURSE "MATHEMATICAL MODELING OF PROCESSES" IN PHARMACY - Marasulov, A.F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The general ideas of modelling as a universal approach to the study of complex objects are used in almost all training courses. Many researchers rightly consider modelling as a general didactic tool and the main method of acquiring knowledge, which determines the importance of purposeful teaching of this method. In this regard, one of the aspects of professional training of students is the formation of knowledge and skills in the use of the method of mathematical modelling. In modern conditions, there are real opportunities to use them in the professional activities of pharmacists. Methods. Systems of structuring the content of education, the formation of intra-subject and inter-subject integration, and types and forms of students’ independent activity. Results. The structuring of the educational content of the course "Mathematical modelling of processes" in pharmacy was carried out, in which mathematical methods were independently identified, and their use in the implementation of technological and production systems in pharmacy. Structural and functional schemes for the formation of the learning content of cycles of lectures and practical tasks have been compiled, which allows you to effectively organize intra-subject and inter-subject integrations, types and forms of students’ independent activities. Conclusion. Important for improving mathematical education are the strengthening of the applied orientation and the individualization of the educational process. The proposed system of teaching the course "Mathematical Models of Processes" in pharmacy will allow students to receive theoretical training and acquire practical skills in the effective use of economic and mathematical models based on modern software for making competent management decisions in their future professional activities.